Integrasi Akidah Dan Akhlak Dalam Pendidikan Islam - Duhana, Tara; Nurmalasari, Nurmalasari; Adanan, Mahdum; Copriady, Jimmy (Universitas Pakuan, 2025)
THE INTEGRATION OF AQIDAH AND AKHLAQ IN ISLAMIC EDUCATIONThis study examines how the integration of faith and morality strengthens character formation in contemporary Islamic education, addressing ongoing issues such as fragmented curricula, weak value internalization, and the separation of theological principles from moral practice. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Articles were retrieved from Google Scholar, Publish or Perish, SINTA 2–4 national journals, and reputable international databases (Scopus and DOAJ). From an initial pool of 167 studies published between 2020 and 2025, ten articles met all inclusion criteria. Data were analyzed using thematic categorization and narrative synthesis to identify recurring patterns across the literature. The review demonstrates that faith consistently provides the theological foundation for ethical orientation, while morality serves as the practical expression of these beliefs. Key themes include: faith as a moral framework, morality as lived behavior, teacher exemplarity and habituation as internalization strategies, and curriculum designs rooted in theological values. The reviewed studies consistently show that character formation cannot rely solely on cognitive instruction; instead, it requires moral practice through habituation and authentic teacher–student engagement. The integration of Islamic values must also respond to digital-era challenges and sociocultural pluralism. The synthesis produces a conceptual model positioning creed as the theological foundation and ethics as its practical manifestation in students’ character development. This study contributes an integrative framework that can serve as a reference for designing adaptive and applicable Islamic character education models across diverse modern school contexts.